Three dimensional simulation of heat transfer problem after cemented hip replacement - Kaorapapong, K.; Jumpen, W.; Amornsamankul, S.; Tang, I.; Wiwatanapataphee, Benchawan (2011)
Total hip replacement involves cement flow interacting with other variables causing heat in the femoral canal. Understanding of heat transfer during cooling after cemented hip replacement is very essential for the surgery. Therefore, this research presents mathematical model and numerical simulation of heat transfer during cooling after cemented hip replacement. The artificial domain is constructed based on real domain using a set of CT scan data of the 65 years old patient. The governing equations are the classical heat transfer equations. The model is solved by finite element method. The temperature across multi-layers of the right artificial domain with implant was carried out.